Transient Changes of Optical Properties in Semiconductors in Response to Femtosecond Laser Pulses - Victor Tkachenko (Applied Sciences, 2016)
In this paper we present an overview of our theoretical simulations on the interaction of ultrafast laser pulses with matter. Our dedicated simulation tool, X-ray induced Thermal And Non-thermal Transitions (XTANT) can currently treat semiconductors irradiated with soft to hard X-ray femtosecond pulses. During the excitation and relaxation of solids, their optical properties such as reflectivity, transmission and absorption, are changing, affected by transient electron excitation and, at sufficiently high dose, by atomic relocations. In this review we report how the transient optical properties can be used for diagnostics of electronic and structural transitions occurring in irradiated semiconductors. The presented methodology for calculation of the complex dielectric function applied in XTANT proves to be capable of describing changes in the optical parameters, when the solids are driven out of equilibrium by intense laser pulses. Comparison of model predictions with the existing experimental data shows a good agreement. Application of transient optical properties to laser pulse diagnostics is indicated.